Islet Amyloid Polypeptide: A Partner in Crime With Aβ in the Pathology of Alzheimer's Disease - Raimundo, Ana F.; Ferreira, Sofia; Martins, Ivo C.; Menezes, Regina (Frontiers in Molecular Neuroscience, 2020)
Diabetes affects hundreds of million people worldwide. Despite the advances in understanding the disease and therapeutic options, it remains one of the leading causes of deaths and of co-morbidities globally. Islet amyloid polypeptide (IAPP), or amylin, is a hormone produced by pancreatic β-cells. It contributes to the maintenance of glucose physiological levels namely by inhibiting insulin and glucagon secretion as well as controlling adiposity and satiation. IAPP is a highly amyloidogenic polypeptide forming intracellular aggregates and amyloid structures that are associated with β-cell death. Also, data suggest the relevance of IAPP unprocessed forms as seeding for amyloid build-up. Besides the known consequences of hyperamylinemia in the pancreas, evidences also point out a pathological role of IAPP in cognitive function. Particularly, IAPP was shown to impair the blood-brain barrier, to interact and to co-deposit with amyloid beta peptide 42 (Aß-42), and possibly with Tau, within the brain of Alzheimer’s disease (AD) patients thereby contributing to diabetes-associated dementia. In fact, it has been suggested that AD results from a metabolic dysfunction in the brain, leading to its proposed designation as Type 3 diabetes. Here, we first provide a brief perspective on IAPP amyloidogenic process and its role on diabetes and AD. We then discuss the potential interventions for modulating IAPP proteotoxicity that can be explored for therapeutics. Finally, we propose to use as guideline for future work the concept of a “diabetes brain phenotype” hypothesis in AD, which may help design future IAPP-centred drug development strategies against AD.